A Different Memory Policy - Budrowska, Kamila (Porównania, 2021)
The reviewed volume, Perceptions of Society in Communist Europe. Regime Archives and Popular Opinion, was written as a part of a long-term project headed by Muriel Blaive, the editor of the publication. The book included a comparative analysis of the history of communism in Czechoslovakia and to a lesser extent also inother countries of the bloc: single articles concerning Poland, Hungary, Romania, Bulgaria and the GDR. The reviewed book complements the existing state of research on communism from a transnational point of view and helps to better understand the experience that was shared by several generations of Central and Eastern Europeans. The author of the article underlines high level of the reviewed publication and draws attention to methodological innovation which is exploit a common experience of citizens of communist countries as a part of scientific inference.